KEPENTINGAN INDONESIA MELAKUKAN EKSPOR KARET ALAM KE JEPANG PADA MASA PEMERINTAHAN JOKOWI (2014-2019) - Siska Destiwansari; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This thesis discusses the interests of Indonesian natural rubber to Japan. Rubber becomes the object of research because it is one of the needs of the world's advanced industrial countries. Natural rubber as an industrial raw material is an Indonesian export commodity that contributes the largest foreign exchange in the non-oil and gas sector from the agricultural sector. Japan is the destination for natural rubber exports because Indonesia is motivated by the natural rubber trade. In analyzing Indonesia's interests in exporting natural rubber to Japan. The author uses a liberalism perspective that is supported by the analysis level of the nation state. The Concept used is the national interest and the International Trade theory. This research is an explanatory qualitative research with descriptive analysis method. The export of Indonesian natural rubber to Japan is a supplier of foreign exchange and a potential market opportunity for Indonesian natural rubber. Japan is a potential market for Indonesian natural rubber. Japan is a developing industrial country that requires rubber exports in the automotive industry. Keywords: Foreign Exchange, Bilateral Relations, Natural Rubber